P‐17: Mutual Interaction of Voltage between Top Gate and Bottom Gate for a‐IGZO TFT. Issue 1 (May 2017) - Gu, Pengfei; Chen, Jiangbo; Xie, Dini; Liu, Wei; Liu, Fengjuan; Sun, Hongda; Song, Young Suk; Yan, Liangchen; Wu, Zhongyuan
Abstract : In this paper, the mutual interaction of gate voltage between top gate and bottom gate in a‐IGZO TFT was investigated. The Vth of top gate (or bottom gate) show a parallel shift with the change of bottom gate (or top gate) voltage. The magnitude of Vth shifts can be described by some approximate analytical expression.